Reliability of the single folding potential to describe the elastic scattering data of the p+43 Ca system - Cheong, L.Y. (American Institute of Physics Inc., 2016)
The study of the elastic scattering potential on the heavy-ions at various incident energies is a method to investigate the nuclear structures and radii. The cluster structure of the heavy-ions is proposed in order to investigate its reaction potentials. Reaction potentials of the heavy-ions have been a puzzle for many years. In this paper, the cluster structure of the heavy-ions is proposed in order to solve this puzzle. Based on this structure the elastic scattering cross-sections of p+43Ca reaction at Ep = 21 - -65 MeV are calculated and the results are in agreement with the experimental data. Â© 2016 Author(s).